Clinical, Histological, and Radiological Outcomes of Sinus Floor Elevation Using a New Approach before Extraction of Periodontally Hopeless Maxillary Molars: A Case Report with 3-year Follow-Up. (15th November 2022) - Yue, Zhaoguo; Liu, Qi; Zhang, Haidong; Yang, Jingwen; Miao, Lili; Hou, Jianxia
Abstract : Introduction . This report is the first to present a case with 3-year follow-up, in which sinus floor elevation was performed before extraction of periodontally hopeless teeth, in order to shorten the edentulous interval between extraction and loading of implants and improve the patient's quality of life. Case Presentation . After a series of initial and supportive periodontal therapies, the lateral window was created at the apices of the hopeless teeth, followed by grafting of bone substitute and membrane material at the sinus floor. The tooth was preserved for 13 months prior to extraction followed by immediate implant placement. The patient is satisfied with the oral function partially retained during the treatment period. Predominance of new bone was detected by histologic analysis. The available bone height was augmented from 1–2 to 12–14 mm with little resorption (less than 2 mm of height) after 3 years of follow-up. The dental implant is in good condition without obvious signs of peri-implantitis or mobility after 3 years of loading. Discussion . The feasibility of modified sinus floor elevation (MSFE) could be seen in the current case. The potential benefit of MSFE may include shortening the edentulous interval, facilitating bone regeneration, and providing a chance for immediate implant placement. However, further clinical case evaluations and controlled studies are required to determine indications, effectiveness, and safety of such augmentation procedures.